A dual-scale FE simulation of hole expansion test considering pre-damage from punching process. (1st February 2022) - Park, Siwook; Cho, Woojin; Jeong, Byeong-Seok; Jung, Jinwook; Sung, Simoon; Na, Hyuntaek; Kim, Sung-Il; Lee, Myoung-Gyu; Han, Heung Nam
Abstract: The effect of the hole-edge condition on the hole-expansion ratio (HER) of ferrite-bainite (FB) dual-phase steel is analyzed by developing a dual-scale finite element (FE) approach. The proposed dual-scale approach consists of macroscale simulation of hole expansion test (HET) and microscale simulation for capturing localized inhomogeneous deformation at the microstructure level. The macroscale HET simulation considers the experimentally measured hole-edge geometry and hardness profile under different clearance conditions. The deformation history in the region of interest calculated from the macroscale simulation was transferred to the microscale simulation as boundary conditions. In the microscale simulation, the deformation inhomogeneity within the two-phase microstructure was calculated by considering the dislocation pile-up at the grain boundaries. In the experimental aspect, the geometry and surface roughness of the hole edge, which are factors for quantifying the damage from the punching process, were measured using a confocal microscope. The work hardening of the material was quantitatively analyzed by measuring the hardness profile in the radial direction from the hole edge. For the work hardening due to the punching process, the measured hardness is converted into an equivalent plastic strain, which is transferred to both macro-and microscale models in the form of pre-strain. The predicted HERs are compared with the experimentally measured HER values, and it is confirmed that the damage caused by punching is critical to the hole expansion formability of the dual-phase FB steel.